An Unusual Intracoronary Honeycomb Pattern in a Patient with Coronary Artery Disease with Dextrocardia - Singh, Ajay P. (J Saudi Heart Assoc, 2021)
This case highlights the diagnostic dilemma and emphasis the role of Optical Coherence Tomography (OCT) to differentiate between spontaneous coronary artery dissection and recanalized thrombus with multiple channels in a patient with dextrocardia.